Changing Patterns of Secondary Employment in Ireland - Williamson, Harry; Coates, Dermot T.; Enright, Shannen; Hogan, Karen (Statistical and Social Inquiry Society of Ireland, 2025)
Over recent years, Ireland’s labour market and economy have outperformed expectations and having successfully weathered the disruption caused by the COVID-19 pandemic, employment levels reached a then record high of 2.64m by mid-2023. In tandem with this expansion of the workforce, the number of those employed in more than one job – or those with secondary employment – has also risen. By mid-2023, 3.5 per cent of persons in employment in Ireland worked multiple jobs, compared to 1.9 per cent in 2002. Despite this increase, Ireland still has one of the lowest rates of secondary employment in the EU27. In absolute terms, by mid-2023, 87,700 persons aged 15-64 years in Ireland were working in two, or more, jobs (compared to 30,000 persons two decades earlier). A further 5,200 persons aged 65 years and over were doing likewise, bringing the total to almost 93,000. Second (or indeed, third) jobs tend to be concentrated in the agricultural and services sectors with the latter having undergone significant expansion in recent years. This paper presents a detailed profile of those in secondary employment. It also considers the intersection between full and part-time work in both a person’s principal and secondary employment and examines patterns in the volume of hours worked.
Read before the Society, 6th March 2025
Keywords: secondary employment; opportunity; necessity; labour markets; Ireland; Europe; 314.15